The excavations of Dashtadem fortress: preliminary report on 2015 fieldwork activity - Melkonyan, Husik; Babajanyan, Astghik; Harutyunyan, Arsen; Davtyan, Davit; Aghaian, Soseh (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
In 2015, according to the agreement with Armenia’s AMAP Human Development NGO, the expedition team of the Institute of Archaeology and Ethnography NAS RA carried out excavations in the territory of the fortress in Dashtadem village (Figure 1/1), in the Aragatsotn region. The area of the excavations is about 1000 m square including the entrance of the first defensive walls and its surrounding territory to the East and North-East (Figure 1/2). The aim of the 2015 excavations was to complete the general structure of the first circle of defensive walls giving opportunity to implement a reconstruction project.